Le féminisme au secours des franchises de science-fiction : le cas de Mad Max : Fury Road (2015) et Ghostbusters (2016) - Marianne Kac-Vergne (ReS Futurae)
This paper examines how a feminist approach can help relaunch flagging science-fiction franchises in the context of what Sarah Banet-Weiser has called today’s “popular feminism” (2018). Ghostbusters (Feig, 2016) and Mad Max: Fury Road (Miller, 2015) are part of the feminization of contemporary franchises insofar as they star female protagonists who lead the action. Yet they go beyond mere increased visibility and adopt a more radical stance since they deal with the structural problems women still have to face in our contemporary society. Such a feminist stance triggered a fierce controversy in the manosphere, which was mainly targeted at the new Ghostbusters. The film fell prey to a violent wave of misogyny in which even Donald Trump participated through a contemptuous tweet. Why was this rage directed more specifically against Ghostbusters than against Mad Max Fury Road? This paper examines the textual differences between the two films, in terms of masculinity notably, but also their different promotional strategies, through an analysis of the press kits and trailers, which can explain such a gap in the films’ receptions.